1997
DOI: 10.1115/1.2842311
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Crack Initiation and Growth in Particulate Composites

Abstract: A micro/macromechanical approach was used to model and simulate crack initiation and crack propagation in particulate composite structures. The approach used both the micromechanical and macromechanical analyses in tandem. The micromechanical analysis was based on a simplified micromechanical model and damage mechanics at the micro-level, and the macromechanical analysis utilized the finite element method. In using these methods, crack initiation and growth in a general shape of composite structure were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Application of strain in the last region of the curve is only to stretch the PMMA and enlarge existing cavities, which is believed to consequently cause the volume growth during loading. Such phenomenon has been studied by many researchers such as Ravichandran and Liu (1995), Kwon et al (1997Kwon et al ( , 1998. These studies investigated the nonlinear constitutive response of a damaged particulate composite in terms of the change in volume dilation and showed that the stress-strain response is nearly linear when there is little or no volume dilatation and the non-linearity sets in once the dilatation becomes significant.…”
Section: Failure Mechanismmentioning
confidence: 99%
“…Application of strain in the last region of the curve is only to stretch the PMMA and enlarge existing cavities, which is believed to consequently cause the volume growth during loading. Such phenomenon has been studied by many researchers such as Ravichandran and Liu (1995), Kwon et al (1997Kwon et al ( , 1998. These studies investigated the nonlinear constitutive response of a damaged particulate composite in terms of the change in volume dilation and showed that the stress-strain response is nearly linear when there is little or no volume dilatation and the non-linearity sets in once the dilatation becomes significant.…”
Section: Failure Mechanismmentioning
confidence: 99%
“…An understanding of the particulate composite failure mechanism is needed both for material characterization, and as a basis for design (Oh and Finnie, 1970;Mori and Tanaka, 1973;Christensen, 1979;Marshall and Evans, 1985;Moshev and Evlampieva, 1997;Wong and Ait-Kadi, 1997a,b;Jones, 1999;Basaran and Jiang, 2002). Many researchers including Achenbach and Zhu (1989), Ju and Chen (1994), Kwon et al (1997, Oshmyan and Muravin (1997), Wong and Ait-Miyano (1997a,b), , Miyano et al (1999), Ju and Sun (2001), Nie and Basaran (2005a), and others have attempted to describe the various damage mechanisms in composites macromechanically or micromechanically. These studies suggested that filler particles play an important role in the mechanical properties of the composite.…”
mentioning
confidence: 99%
“…Application of strain in the last region of the stress-strain curve is only to stretch the PMMA matrix and enlarge existing cavities, which consequently causes volume growth during loading. Such a phenomenon has been studied by many researchers such as Kwon et al (1997, Moshev and Evlampieva (1997), Oshmyan and Muravin (1997), and Ravichandran and Liu (1995). These studies investigated the nonlinear constitutive response of a damaged particulate composite in terms of the change in volume dilation, and showed that the stress-strain response starts to behave nonlinearly at the point where the volume dilatation begins to increase.…”
mentioning
confidence: 99%
“…Theoretically, such research can be done with well-established computational techniques such as finite element methods. Even with the impressive computational power that is currently available, such detailed micromechanical simulations are not feasible because of the need for ultrafine meshes and computationally demanding remeshing procedures (5). Furthermore, considering the main objective of characterizing the fatigue behavior at a macro level, it is unnecessary to resort to such detailed micromechanical modeling.…”
mentioning
confidence: 99%